KEMAMPUAN MAHASISWA PENDIDIKAN MATEMATIKA DALAM MEMECAHKAN MASALAH DI AWAL DAN AKHIR SEMESTER PERTAMA - Jackson Pasini Mairing (Universitas Jenderal Soedirman, 2017)
Problem solving ability is main goal of students in learning mathematics. Lectures should be able to improve the ability. This reasearch aimed to describe ability ofstudents at the beginning and end of first semester academic year 2016/2017 in solving mathematical problems. The research subjects were 71 students of mathematicseducation program class of 2016 from one of the universities in Central Kalimantan, Indonesia. At the beginning and the end of first semester, each subject was given sixmathematical problems. The problems at the beginning and the end of semester were similar only differently in numbers. The result showed that average score of the students at the beginning and the end of first semester were 7.97 and 9.18 (scale 0 - 24), respectively. The scores increased significantly with a 95% confidence level. Theincreasng caused 8.4% of the students who were classified as naive problem solvers increased their ability becomed routine problem solvers. No students have improved their ability becomed good problem solvers.